Delayed prolongation of the QRS interval in patients with left ventricular dysfunction. (1st December 2019) - Rav-Acha, Moshe; Nujidat, Ali; Farkash, Rivka; Medina, Aharon; Ilan, Michael; Klutstein, Marc; Butnaru, Adi; Weitsman, Tatyana; Glikson, Michael; Hasin, Tal
Abstract: Aims: Patients with left ventricular dysfunction (LVD) and prolonged QRS on surface electrocardiogram are at increased risk for heart failure and death and may benefit from resynchronization therapy. Patients with initial narrow QRS may prolong their QRS during the disease course. The occurrence of delayed QRS prolongation, its predictors and associated risk of heart failure hospitalizations (HFH) or death are currently unknown and the subject of this investigation. Methods & results: Patients with LVD, QRS < 120 ms and available follow-up ECGs were retrospectively evaluated for persistent unprovoked QRS prolongation >130 ms. Impact on mortality or HFH was assessed using Cox regression with QRS > 130 ms as a time dependent covariate. Following 178 patients for 30 (10;59) median (IQR) months, 28 (16%) patients prolonged their QRS to >130 ms, reaching a QRS duration of 154 ± 29 ms; LBBB pattern was diagnosed among 14 (50%) patients. Patients with delayed QRS prolongation were older (71.9 ± 11.8 vs 64.4 ± 15.1 years p  = 0.014), had larger left ventricle and left atrial diameters (6.3 ± 0.9 vs 5.7 ± 0.9 cm p  = 0.010; 4.9 ± 0.6 vs 4.5 ± 0.7 cm p  = 0.006, respectively) and wider baseline QRS (104.8 ± 12.6 vs 91.4 ± 14.5 ms p  < 0.001) which was linearly associated with late QRS prolongation (p for trend<0.0001). In a multivariable model, age, baseline QRS width and left atrial diameter were significantly associated with delayed QRS prolongation. QRS prolongation at follow-up was independently associated with risk of death or HFH (HR 7.426, 95% CI3.017–18.280, p  < 0.0001). Conclusion: QRS prolongation occurs in a significant proportion of patients with LVD and portends adverse outcome. Advanced age, prolonged QRS and larger left atria are potential predictors. Routine monitoring is justified and physicians may choose to plan ahead for resynchronization therapy in patients at risk for QRS prolongation. Highlights: QRS width in patients with LV dysfunction is dynamic and may prolong significantly over time 16% of patients with LV dysfunction and narrow QRS prolong their QRS during follow up A linear correlation exists between baseline QRS and probability for delayed QRS prolongation Age, baseline QRS width, and LA diameter are probable predictors for delayed QRS prolongation QRS prolongation at follow-up was independently associated with a combined risk of death or heart failure hospitalizations